Efficiency Analysis of Tuna Fish Floss Product Marketing Channels at Rubons MSMEs in North Sinjai District: Analisis Efisiensi Saluran Pemasaran Produk Abon Ikan Tuna pada UMKM Rubons di Kecamatan Sinjai Utara - Riska Baso; Megawati; Fadilah Nurdin (Jurnal Ilmiah Manajemen Agribisnis, 2026)
This study aims to analyze the marketing channels and the level of marketing efficiency of tuna floss products at UMKM Rubons, located in Kelurahan Lappa, Sinjai Utara District. The method used is descriptive quantitative with a case study approach. Data were obtained through interviews, questionnaires, and direct observations with the business owner and distributor. The results show that UMKM Rubons uses two types of marketing channels: direct and indirect. The direct channel provides greater profits to producers because it involves no intermediaries, while the indirect channel offers a broader marketing efficiency value (EP) of 4.44% indicates that the marketing channels used are highly efficient, as the value is below the 50% threshold. The main obstacle faced is the low interest from consumers ang the lack of promotional strategies.